MICROARTRÓPODOS ASOCIADOS A VEGETACIÓN DE NEBLINA. PROVINCIA DE ANTOFAGASTA, CHILE - Covarrubias, René; Toro, Haroldo (Acta Entomológica Chilena, 2022)
A field study was conducted on a fog-dependent vegetation zone, near the coast, on the deseitic regions north of Chile; 3 different valleys were sampled: Paposo, Taltal and Cifuncho (23° 25’ Lat. S; 70° 30’ Long. W). Microarthropods were sampled under 16 plant species and on soil without vegetation. Sampling was repeated on 6 different dates, along 1993, 1994 and 1995. Results, based on the study of 233 soil samples, treated by means of Berlese-Tullgren funnels, show a typical microarthropod composition, with 26 supraspecific taxa, among which the dominant ones are Prostigmatid and Cryptostigmatid mites, and Psocopteran insects; this for xerophytic conditions; in a different hydrophytic situation other taxonomic structure was found, where Collembola and insect larvae were the dominant ones. Data on sample frequency (%) and mean densities are given for each taxon and plant species. Working with these most frequent taxa, Kruskal-Wallis tests show for Oribatids, Prostigmatids, Psocoptera and also the total fauna, very significant differences in their abundances, depending on the plant species factor. Otherwise, one-way analysis of variance on the above cited most frequent taxa show that the sample date factor was significant in 5 cases for Oribatids, in 3 cases for Prostigmatids and in 4 cases for Psocopterans; all three taxa show significant sampling time variations under Nolana ciivata and Dinemandra ericoides; only 2 of them vary significantly under G ypotham nium pinifolium and Eulychnia breviflora; also, only Psocoptera varied significantly under Lycium fra g o su m and in bare soils. Another two-way analysis of variance, shows no significance for either factor (valley; sampling date) with data from Oribatid mites, Psocoptera or Total fauna. Prostigmatid mites, on the contrary, shows significance for both factors but no for interaction.